Vocational Didactics: Core Assumptions and Approaches from Denmark, Germany, Norway, Spain and Sweden - Gessler, Michael; Moreno Herrera, Lázaro (International Journal for Research in Vocational Education and Training, 2015)
The design of vocational didactics has to meet special requirements. Six core assumptions are identified: outcome orientation, cultural-historical embedding, horizontal structure, vertical structure, temporal structure, and the changing nature of work. Different approaches and discussions from school-based systems (Spain and Sweden) and dual systems (Denmark, Germany and Norway) are presented in this special issue. From an inside or national perspective, the solutions show a high cultural-historical dependency. From an outside or cross-national perspective, contingency and alternative possibilities become visible. The combination of both perspectives could enable continuity as well as innovation. This is the basic assumption of the presented collection about vocational didactics.